EFEKTIVITAS MODEL CIRC BERBANTUAN BUKU CERITA DIGITAL DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK SEKOLAH DASAR - Avril Lavina Putri, Cinta; Mega Diana, Siska; Dian Putra, Agung; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low reading comprehension ability of students. This study aims to determine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by digital storybooks in improving the reading comprehension ability of elementary school students. The research method used is a quasi-experimental design with Nonequivalent Control Group De-sign. Data were collected through test instruments and analyzed using the Inde-pendent Sample T-Test and the score improvement test (N-Gain score). The re-sults of the study showed a significant difference between the experimental class and the control class. Students who learned using the CIRC model assisted by digi-tal storybooks showed a higher increase in reading ability compared to students who used the Think Pair Share (TPS) model. Thus, the CIRC model assisted by digital storybooks is effective in improving the reading comprehension ability of el-ementary school students.